Effect of summer legumes on growth and yield of lowland rice (Oryza sativa) and its residual effect on succeeding wheat (Triticum aestivum) in rice-wheat system - Mahapatra, B S; Sharma, G L (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during 1990-91 and 1991-92 on a silty clay-loam soil to study the effect of summer legumes on growth and yield of rice (Oryza sativa L.) and its residual effect on succeeding wheat (Triticum aestivum L. emend. Fiori & Paol.). Summer cropping of prickly sesban or dhaincha [Sesbania cannabina (Retz.) Pers.] for green-manure and of cowpea [Vigna unguiculata (L.) Walp.] for fodder had significant effect on growth, yield and nitrogen uptake of rice crop. Mean data of 2 years showed that green-manure crop (helping produce 5.1 tonnes/ha rice grain) and fodder cowpea (helping produce 4.3 tonnes/ha rice grain) could contribute equivalent to 90 and 60 kg N/ha supplied through prilled urea respectively in lowland transplanted rice. The mean yields obtained with 120 kg N/ha applied through prilled urea(6.50 tonnes/ha) and dhainchaÂ green-manuring + 30 kg N/ha through prilled urea(6.45 tonnes/ha) were at par. The difference in yield and nitrogen uptake by rice could be attributed to significant difference in ammonium-N of the soil at tillering and panicle-initiation stages, and was significantly positive. Summer cropping of Sesbania and cowpea significantly increased tile yield and nitrogen uptake byÂ the succeeding wheat compared with 120 kg N/ha applied to rice through prilled urea. This could be attributed to significant positive correlation with available soil N at rice harvesting and nitrate production at the time of planting.